Intrathecal chemotherapy for the management of lymphoblastic lymphoma in a 4-year-old dog: a case report - Lyseight, Filipa Louise Simões; Dupont, Christophe Osterreicher Cunha; Cherubini, Giunio Bruto (Frontiers in Veterinary Science, 2023)
Intrathecal chemotherapy is used in human medicine for treatment or prophylaxis of CNS hematopoietic neoplasia. However, the clinical benefit in veterinary medicine is scarcely documented.A 4-year-old, male entire, cross breed dog, presented with a 24-hour history of severe lethargy, pelvic limb weakness and urinary retention. Examination revealed generalised peripheral lymphadenomegaly and neurological findings were compatible with T3-L3 myelopathy. Following the diagnosis of multicentric lymphoblastic B-cell lymphoma (stage Vb) a modified L-LOP with cytosine arabinoside was started and complete clinical remission was achieved. After four weeks there was acute neurological deterioration (spinal pain and proprioceptive deficits) without peripheral lymphadenomegaly. MRI findings and CSF analysis were consistent with meningeal and spinal cord lymphoma infiltration at the level of L3. Intrathecal chemotherapy (cytosine arabinoside and methotrexate) was administered in the cisterna magna, with systemic dexamethasone and analgesia.Resolution of clinical signs was achieved within twenty-four-hours and the patient remained asymptomatic for 3.5 weeks. CNS relapse was suspected after this period (proprioceptive deficits and severe thoracolumbar pain) and repeat intrathecal chemotherapy was declined. The patient was humanely euthanized nine weeks after diagnosis. This is the first report on the clinical benefit of intrathecal chemotherapy with a combination of methotrexate and cytarabine for management of CNS 2 This is a provisional file, not the final typeset article lymphoma in dogs. Based on our case, intrathecal chemotherapy with methotrexate and cytarabine can induce a short-lasting CNS clinical remission (3 weeks).